2019
DOI: 10.1038/s41467-019-10102-6
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor CBFB suppresses breast cancer through orchestrating translation and transcription

Abstract: Translation and transcription are frequently dysregulated in cancer. These two processes are generally regulated by distinct sets of factors. The CBFB gene, which encodes a transcription factor, has recently emerged as a highly mutated driver in a variety of human cancers including breast cancer. Here we report a noncanonical role of CBFB in translation regulation. RNA immunoprecipitation followed by deep sequencing (RIP-seq) reveals that cytoplasmic CBFB binds to hundreds of transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 34 publications
4
69
0
Order By: Relevance
“…Our study establishes that inhibition of RUNX1 DNA binding through pharmacological disruption of the RUNX1-CBFβ interaction specifically elicits an epithelial-to-mesenchymal transition that accompanies changes in critical genes and pathways involved in EMT. Recent findings have identified a non-canonical, posttranscriptional role for CBFβ in mammary epithelial cells [26]. Our results indicate that, in addition to posttranscriptional regulation of gene expression, CBFβ plays important roles in transcriptional activity of DNA binding members of the RUNX family.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study establishes that inhibition of RUNX1 DNA binding through pharmacological disruption of the RUNX1-CBFβ interaction specifically elicits an epithelial-to-mesenchymal transition that accompanies changes in critical genes and pathways involved in EMT. Recent findings have identified a non-canonical, posttranscriptional role for CBFβ in mammary epithelial cells [26]. Our results indicate that, in addition to posttranscriptional regulation of gene expression, CBFβ plays important roles in transcriptional activity of DNA binding members of the RUNX family.…”
Section: Discussionsupporting
confidence: 51%
“…Conversely, several studies have shown that lineage restricted depletion of CBFβ only partially recapitulates phenotypes observed with deletion of the DNA binding RUNX factors [19,[22][23][24][25], suggesting that not all transcriptional regulatory activity of these proteins requires CBFβ. Furthermore, a recent study has shown that CBFβ functions post-transcriptionally to regulate gene expression in breast epithelial cells [26]. Together, these observations highlight knowledge gaps in the mechanistic understanding of gene regulation by the RUNX-CBFβ transcriptional complex.…”
Section: Introductionmentioning
confidence: 84%
“…Pathway analysis of breast cancer genes shows enrichment of pathways involved in gene expression regulation governed by TP53, RUNX1 and PTEN which includes pathways that regulates estrogen-mediated transcription. CBFB deletion leads to expression loss of RUNX1[21], which can no longer regulate NOTCH signalling by repression, which is confirmed by pathway analysis. Some apoptosis pathways are enriched that include CDH1 and TP53 genes.…”
Section: Resultsmentioning
confidence: 92%
“…Genes identified for breast cancer was validated by supporting literature. CBFB [21] and PTEN [22, 23] is a known TSG in breast cancer. PTEN is found to be under-expressed in breast cancer [24, 25].…”
Section: Resultsmentioning
confidence: 99%
“…It encodes a transcription factor, which makes a complex by attaching to RUNX1 2 . This complex can transcriptionally repress the oncogenic NOTCH signaling pathway (Malik et al, 2019). TBX3 is a substantial gene in Primary subtype, which is needed for normal breast development 3 .…”
Section: Finding the Gene Signature For Each Subtypementioning
confidence: 99%